ANALISIS PERUBAHAN PITA FREKUENSI 1800 DAN 2100 MHZ TERHADAP PERFORMANSI JARINGAN BASE TRANSCEIVER STATION - Syarif Muhammad Faisal . (Faculty of Engineering, Universitas Tanjungpura, 2017)
Abstract - In its application, the mobile system has its limitations and is often experienced disturbances (interference) like limited talk channels as the result of the increasing number of cellular communication technology user, which is led to „block call‟. The problem with Radio Frequency (RF) signal reception is also an important factor in wireless communication system. The low quality of signal levels caused the frequent call failure or „drop call‟. Therefore, it is necessary to have sustainable monitoring system and analysis towards the performance of the network system, especially after the government produce the For a review of Necessary Process Monitoring and analysis of the Sustainable Network system, especially with the regulation of the Ministry of Communication and Information No. 19 / 2013 About